Differential delivery dates, retrievability and the incentives compatibility of contracts - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2015)
Differential delivery dates (D3) of contract obligations characterize most contracts in real life. D3 puts the contractor who delivers last, in the words of David Hume (1769), in "a position of advantage" because reneging on his/her obligation can be profitable. Ex-ante remedies such as Coase's 'ownership', Williamson's 'hostage', Klein et al's "vertical ownership", Grossman and Hart's "assignment of residual rights", etc have been proposed. The principal's decision to appropriate the quasi-rent generated by the agent delivering effort first under possibly weak public ordering and non-zero retrievability of delivered effort is explicitly modeled. We give the sufficient conditions for the preservation of the incentives compatibility of the simple P-A effort-in-advance contract in the D3 environment.
Keywords: D52; D86; 330; incentives compatibility; quasi-rent appropriation; retrievability; incentives contract